Rétrospective sur la voix de la rue au Maroc : Tout ne change pas pour ne rien changer - Mounia Bennani-Chraïbi (L’Année du Maghreb)
In Morocco, the relative liberalisation of the authoritarian regime combined with the management of the “years of lead” have contributed to transforming the modulations of the “voice of the street”, without however “defusing” its disruptive character. They even seem to have produced unexpected effects: a modular repertoire; a strengthening of the coordination of collective actions; a protest arena more autonomous and structured around the issue of the conflict opposing the centre and an unified periphery. In other words, in Morocco, not everything changes so that nothing changes.